2012
DOI: 10.1371/journal.pone.0034621
|View full text |Cite
|
Sign up to set email alerts
|

Cdt1 Is Differentially Targeted for Degradation by Anticancer Chemotherapeutic Drugs

Abstract: BackgroundMaintenance of genome integrity is crucial for the propagation of the genetic information. Cdt1 is a major component of the pre-replicative complex, which controls once per cell cycle DNA replication. Upon DNA damage, Cdt1 is rapidly targeted for degradation. This targeting has been suggested to safeguard genomic integrity and prevent re-replication while DNA repair is in progress. Cdt1 is deregulated in tumor specimens, while its aberrant expression is linked with aneuploidy and promotes tumorigenes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
9
1

Relationship

4
6

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 50 publications
1
19
0
1
Order By: Relevance
“…Indeed, it has been shown already that accumulated CDT1, because of reduced degradation results in DNA rereplication and cell apoptosis [39]. It has been also shown that CDT1 destruction occurs in cells after treatment with chemotherapeutics [46] and after UV irradiation [47, 48]. We report here that in cancer cells, but not in non-transformed cells, this mechanism was consistently impaired by CDT2 depletion.…”
Section: Discussionsupporting
confidence: 61%
“…Indeed, it has been shown already that accumulated CDT1, because of reduced degradation results in DNA rereplication and cell apoptosis [39]. It has been also shown that CDT1 destruction occurs in cells after treatment with chemotherapeutics [46] and after UV irradiation [47, 48]. We report here that in cancer cells, but not in non-transformed cells, this mechanism was consistently impaired by CDT2 depletion.…”
Section: Discussionsupporting
confidence: 61%
“…DNA damage was induced by treating cells with etoposide, a topoisomerase inhibitor producing DNA strand breaks (32), to enhance degradation of Mdm2 (Fig. S4A).…”
Section: Resultsmentioning
confidence: 99%
“…[22][23][24] When cells are exposed to irradiation or other DNA-damaging reagents, Cdt1 is degraded via the same PCNA-and CRL4 Cdt2 -dependent pathways. [25][26][27][28][29][30] Exposure of cells to UV (UV) irradiation induces helix-distorting DNA lesions, such as cyclobutane pyrimidine dimers (CPDs) and 6-4 pyrimidine-pyrimidone photoproducts. Upon UV irradiation, Cdt1 is rapidly degraded within minutes, primarily dependent on the nucleotide excision repair (NER) process, 31,32 based on the finding that Cdt1 degradation is attenuated when xeroderma pigmentosum (XP)-related proteins are inactivated or depleted.…”
Section: Q-x-x-[i/l/m/v]-t-d-[f/y]-[f/y]-x-x-[k/r]-[k/r] (Pip Boxmentioning
confidence: 99%